REVALUASI ASET TETAP DENGAN LIKUIDITAS SEBAGAI VARIABEL MODERATING (STUDY PADA PERUSAHAAN SEKTOR PROPERTY, REAL ESTATE, AND BUILDING CONSTRUCTION YANG TERDAFTAR DI BEI 2017-2019) - Satriawan, Andhika; Baroroh, Niswah (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2021)
This research objective was to examine the effect of Cash Flow from Operation, Fixed Assets Proportion, and Company Growth on Revaluation Decision, Moderated by Liquidity. This research, used as the property, real estate, and construction company listed to IDX from 2017 to 2019, by purposive sampling of 84 companies. From this research, it was known that cash flow and company growth did not influence revaluation. Fixed asset proportion positively influenced fixed asset revaluation decision. Liquitidy variable did not become moderating variable toward cash flow from operation, but was proven as a moderating variable of the link between fixed asset proportion and company growth on revaluation decision. Variable cash flow and company growth did not affect revaluation. Liquitidy was not proven moderate cash flow from operation toward asset revaluation, but was proven as a moderating variable of fixed asset intensity and company growth toward fixed asset revaluation.